Understanding COVID-19 birth-pangs’ theological responses and the promised Parousia of Jesus - Ukeachusim, Chidinma P. (2024)
Jesus in Matthew 24 presaged to his disciples about the eschatological birth-pangs that would be occurring in the world in the interim of his departure and his promised Parousia and the end of this age. It is a theological concern how the disciples of Jesus in every era are to be responding to eschatological birth-pangs in the light of Jesus’ promised Parousia. This study is based on the existential reality that many Nigerian professing Christians do not understand how they are to be responding to an eschatological birth-pang like coronavirus disease 2019 (COVID-19) pandemic in relation to the promised Parousia of Jesus. How then are the elects in Nigeria to be responding to eschatological occurrence like COVID-19 and as well be preparing for the Parousia of Jesus? Therefore, using redaction criticism approach of conducting biblical exegesis, this study focusses on theologically interpreting the context of Matthew 24:15−51, to unveil and recommend pragmatic theological Christian responses that underline how Nigerian Christians are to be righteously responding to the COVID-19 pandemic as an eschatological birth-pang, and as well be preparing for the promised Parousia of Jesus. Intradisciplinary and/or interdisciplinary implications: In the Olivet-discourse, Jesus in advance informed his disciples how they are to be responding to the birth-pangs, and also be preparing for his Parousia. This study explored Matthew 24:15−51 and unveils how the church in Nigeria is to be responding to the COVID-19 pandemic as an eschatological birth-pang in the light of Jesus’ promised Parousia.
Keywords: Covid-19 Pandemic; Matthew 24:15−51; Nigeria; Parousia; Church; Eschatology